Synthesis of Polydopamine Hollow Capsules via a Polydopamine Mediated Silica Water Dissolution Process and Its Application for Enzyme Encapsulation - Tran, Huy Quang; Bhave, Mrinal; Xu, Guowang; Sun, Chenghua; Yu, Aimin (Frontiers in Chemistry, 2019)
Herein, we present a systematic study on the preparation of polydopamine (PDA) hollow capsules by templating silica particles which were subsequently removed by a PDA mediated water dissolution process without using any harsh chemical treatment. It was found that the time required for silica removal varied depending on the PDA coating and dissolution conditions. Factors that could influence the core removal process including the thickness and temperature of PDA coating, silica calcination duration and the availability of water were then examined in detail. Additionally, catalase was used as a model enzyme to be encapsulated into PDA hollow capsules and its bio-functionality was found to remain active. The result also indicated that the as-synthesized PDA capsules possessed a porous structure, which allows the penetration of small molecules such as H2O2. This study offers a better insight into silica dissolution process mediated by PDA, and contributes to the development of an eco-friendly approach for the fabrication of hollow capsules that have promising applications in drug delivery systems.